An electrolyte for electrolytic capacitors
By plasma treatment of silicon carbide and compounding with polyhydroxy polycarboxylic acid, the problem of existing electrolytes being difficult to maintain high conductivity and stability while improving flash fire voltage and low-temperature working performance, achieving higher flash fire voltage and capacitor life.
Patent Information
- Application Number
- CN202411733903.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
While the existing aluminum electrolytic capacitor electrolytes improve flash fire voltage and low-temperature working performance, it is difficult to maintain high conductivity and stability, especially under high-temperature storage conditions.
By plasma treatment of silicon carbide and compounding with polyhydroxy polycarboxylic acid, a synergistic effect is formed to increase the flash fire voltage of the electrolyte and the life of the capacitor.
It significantly improves the flash fire voltage of the electrolyte and the service life of the capacitor, while maintaining the stability of high conductivity, especially under high temperature conditions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolyte for electrolytic capacitors, and in particular to an electrolyte for electrolytic capacitors. Background Art
[0002] Aluminum electrolytic capacitors are columnar capacitors that use metal oxide film as a dielectric to form a three-layer winding structure of metal oxide positive foil, electrolytic paper, and negative foil. Metal aluminum leads are used as lead-out ends and are immersed in the corresponding electrolyte to form passive components that can be used for filtering. In recent years, aluminum electrolytic capacitors have gradually occupied most of the capacitor market due to their lower prices and higher specific capacitance. At present, aluminum electrolytic capacitors have been widely used in industries such as laptops, aerospace, precision instruments, and automotive electronics. Therefore, the comprehensive performance requirements of aluminum electrolytic capacitors are also getting higher and higher.
[0003] The working electrolyte of aluminum electrolytic capacitors is the actual negative electrode, so the electrolyte occupies an extremely important position in aluminum electrolytic capacitor products. It affects whether the product can work normally for a long time and has the function of optimizing the electrical performance of the capacitor. The working electrolyte of aluminum electrolytic capacitors is mainly composed of solvents, solutes, dehydrogenation agents, waterproofing agents and other additives. Generally speaking, increasing the solubility of solutes is conducive to improving conductivity and improving the low-temperature working performance of the electrolyte. Adding a flash voltage enhancer helps to increase the flash voltage of the capacitor. CN114783777A discloses a high-voltage aluminum electrolytic capacitor and an electrolyte. The electrolyte comprises, by mass, 40-55 parts of ethylene glycol, 3-8 parts of solute, 2-8 parts of anti-hydration agent, 5-10 parts of dehydrogenating agent, 5-15 parts of viscosity regulator and 2-10 parts of modified polyethylene glycol succinate; the modified polyethylene glycol succinate is prepared from raw materials including 1-5 parts of nano silicon dioxide, 5-15 parts of polyethylene glycol and 5-15 parts of succinic acid. The method uses ethylene glycol as a main solvent and compounding additives such as modified polyethylene glycol succinate and dehydrogenating agent to improve the conductivity and flash voltage of the electrolyte. CN112908703A discloses an anti-corrosion electrolyte for electrolytic capacitors, which comprises, by mass, 10 to 30 parts of ethylene glycol, 5 to 10 parts of ammonium adipate, 1 to 8 parts of ammonium formate, 1 to 5 parts of additives, and 1 to 3 parts of ultrapure water. The additive is nitrogen-doped nano-silicon dioxide, which significantly reduces the risk of corrosion of internal components of the capacitor and increases its service life.
[0004] Therefore, it is necessary to add additional additives to provide high-performance aluminum electrolytic capacitor electrolyte. Summary of the invention
[0005] In order to overcome the problems existing in the prior art, the present invention provides an electrolyte for an electrolytic capacitor, which comprises, by mass,
[0006] 60-80 parts of solvent, 15-25 parts of solute, 0.1-0.5 parts of waterproof mixture, 0.1-0.5 parts of hydrogen remover, 0.5-2 parts of flash voltage enhancer;
[0007] Wherein, the flash voltage enhancer comprises polyhydroxy polycarboxyl organic acid and plasma treated silicon carbide.
[0008] Furthermore, the method for preparing plasma-treated silicon carbide comprises:
[0009] After the silicon carbide is washed for 1 to 10 minutes in a mixed gas of oxygen and / or argon at a gas flow rate of 100 to 200 mL / min, it is treated for 1 to 10 minutes at a voltage peak of 1 to 10 kV using dielectric barrier discharge to obtain plasma-treated silicon carbide.
[0010] The flash voltage of the electrolyte is related to the viscosity and the amount of flash voltage enhancer used. In addition, the flash voltage of the electrolyte has a very direct relationship with its conductivity. It is difficult to increase the flash voltage while ensuring sufficient conductivity. Conventional flash voltage enhancers include: 1. Polyhydroxy macromolecular substances, such as polyethylene glycol, polyvinyl alcohol, etc., which use the anode foil oxide film to have a strong adsorption effect on macromolecules or polymers to increase the flash voltage; 2. Small molecules containing polyhydroxy and carboxyl groups, such as citric acid and tannic acid, can form a stable "interlayer" with the oxide film under the action of the electric field force, which can effectively increase the flash voltage; 3. Nanoparticles, such as silicon dioxide, manganese dioxide, etc., can be adsorbed into the pores on the surface of the anode oxide film, effectively increasing the flash voltage of the electrolyte. However, due to its filling effect, the electrolyte is unstable during high-temperature storage, resulting in a decrease in the electrolyte flash voltage.
[0011] The design concept of the present invention is: based on the currently commonly used electrolytic capacitor components, without introducing other organic substances to modify silicon carbide, silicon carbide is plasma treated. During the plasma strengthening process, high-energy plasma can interact with the surface of silicon carbide to form a special structure and chemical state on the surface of silicon carbide, thereby improving the surface properties of silicon carbide. The results show that plasma-treated silicon carbide and polyhydroxy-polycarboxyl organic acids have a good synergistic effect, which increases the flash voltage of the electrolyte and increases the life of the capacitor.
[0012] Furthermore, the particle size of the silicon carbide is 0.02-5 μm.
[0013] Furthermore, the mass ratio of the polyhydroxy-polycarboxyl organic acid to the plasma-treated silicon carbide is 1-5:1.
[0014] Furthermore, the polyhydroxy-polycarboxyl organic acid includes at least one of malic acid, citric acid and tannic acid.
[0015] Furthermore, the solvent includes at least one of ethylene glycol, propylene glycol, glycerol, diethylene glycol, and n-butanol.
[0016] Furthermore, the solute includes at least one of ammonium adipate, ammonium hydrogen azelaate, ammonium dodecanedioate, and ammonium sebacate.
[0017] Anti-hydration agents can inhibit hydration in the electrolyte system, repair the dielectric film, reduce the generation of leakage current, increase the flash voltage of the electrolyte, and thus extend the service life of aluminum electrolytic capacitors.
[0018] Furthermore, the waterproof mixture includes at least one of polymethacrylic acid, phosphoric acid, ammonium phosphate, hypophosphorous acid, ammonium hypophosphite, phosphorous acid, and ammonium phosphite.
[0019] Hydrogen removers can reduce the concentration of hydrogen ions in the electrolyte system, effectively reduce the hydrogen in the electrolyte, and reduce the phenomenon of capacitor failure caused by the increase of internal pressure in aluminum electrolytic capacitors. Hydrogen removers are generally selected as nitro compounds.
[0020] Furthermore, the hydrogen remover includes at least one of nitrobenzyl alcohol, p-nitrobenzoic acid, resorcinol, o-nitroanisole, and m-nitroacetophenone.
[0021] The present invention also provides an aluminum electrolytic capacitor, comprising a hollow structure shell, an anode foil, a cathode foil and a lead wire, wherein the anode foil and the cathode foil are parallel to each other and penetrate the shell, the anode foil and the cathode foil are led out by the lead wire, and the shell stores the above-mentioned electrolyte for the electrolytic capacitor.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention performs plasma treatment on silicon carbide without introducing other organic substances to modify silicon carbide. During the plasma strengthening process, high-energy plasma can interact with the surface of silicon carbide to form a special structure and chemical state on the surface of silicon carbide, thereby improving the surface properties of silicon carbide. The results show that plasma-treated silicon carbide and polyhydroxy-polycarboxyl organic acids have good synergistic effects, improve the flash voltage of the electrolyte, and increase the life of the capacitor. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0025] Some of the raw materials used in the embodiments of the present invention are described as follows:
[0026] Silicon carbide, average particle size: 40nm, cubic structure, specific surface area: 20-30m 2 / g, bulk density: 0.05g / cm 3 .
[0027] Other raw materials not mentioned are common raw materials in the art. The above content is only to help illustrate the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase or prepare the same / similar raw materials from the market. These contents will not be repeated in the examples.
[0028] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0031] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0032] S2, at a rotation speed of 200 rpm, add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid, 0.7 g of tannic acid, and 0.7 g of plasma-treated silicon carbide to the mixed solution prepared in step S1, heat to 120° C., stir for 30 min, and then naturally cool to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0033] Wherein, the preparation method of plasma treated silicon carbide is:
[0034] (1) A mixed gas of oxygen and argon was selected as the background gas for plasma treatment. First, a gas washing process was performed inside the chamber. The gas washing process was completed using a DC flow controller. The flow ratio of oxygen to argon was 1:9 and lasted for 5 minutes. The total gas flow rate was maintained at 100 mL / min.
[0035] (2) Turn on the high-frequency sinusoidal AC power supply to start plasma treatment, adopt dielectric barrier discharge, and use parallel plate electrodes; the type of barrier medium is quartz glass; the dielectric barrier method is high-voltage pole-ground electrode double barrier, the power frequency is set to 12 kHz, the voltage peak is set to 8 kV, and the treatment time lasts for 5 minutes to obtain plasma-treated silicon carbide.
[0036] Example 2
[0037] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0038] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0039] S2, at a rotation speed of 200 rpm, add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid, 1.05 g of tannic acid, and 0.35 g of plasma-treated silicon carbide to the mixed solution prepared in step S1, heat to 120° C., stir for 30 min, and then naturally cool to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0040] The preparation method of plasma-treated silicon carbide is the same as that in Example 1.
[0041] Example 3
[0042] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0043] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0044] S2, at a rotation speed of 200 rpm, add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid, 1.12 g of tannic acid, and 0.28 g of plasma-treated silicon carbide to the mixed solution prepared in step S1, heat to 120° C., stir for 30 min, and then naturally cool to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0045] The preparation method of plasma-treated silicon carbide is the same as that in Example 1.
[0046] Comparative Example 1
[0047] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0048] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0049] S2, adding 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid and 1.4 g of tannic acid to the mixed solution prepared in step S1 at a rotation speed of 200 rpm, heating to 120° C., stirring for 30 min, and then naturally cooling to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0050] Comparative Example 2
[0051] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0052] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0053] S2. Add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid and 1.4 g of silicon carbide to the mixed solution prepared in step S1 at a rotation speed of 200 rpm, heat to 120° C., stir for 30 min, and then cool naturally to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0054] Comparative Example 3
[0055] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0056] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0057] S2, at a rotation speed of 200 rpm, add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid, 1.05 g of tannic acid, and 0.35 g of silicon carbide to the mixed solution prepared in step S1, heat to 120° C., stir for 30 min, and then naturally cool to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0058] Comparative Example 4
[0059] A method for preparing an electrolyte for an electrolytic capacitor, comprising the following steps:
[0060] S1, 70g ethylene glycol, 5g ammonium dodecanedioate, and 15g ammonium sebacate were mixed at a speed of 150rpm, and the temperature was raised to 60°C, and stirring was continued until they were completely dissolved to obtain a mixed solution;
[0061] S2. Add 0.3 g of ammonium hypophosphite, 0.4 g of p-nitrobenzoic acid and 1.4 g of plasma-treated silicon carbide to the mixed solution prepared in step S1 at a rotation speed of 200 rpm, heat to 120° C., stir for 30 min, and then naturally cool to 25° C. to obtain an electrolyte for an electrolytic capacitor.
[0062] The preparation method of plasma-treated silicon carbide is the same as that in Example 1.
[0063] Test Case
[0064] The conductivity of the electrolytes prepared in the embodiments and comparative examples at 30°C was tested using a desktop conductivity tester; the flash voltage of the electrolytes prepared in the embodiments and comparative examples at 30°C was tested using a Yangzhou Baoou TV-1CH intelligent TV tester, and the test area was 5cm 2 Anode foil, current density is 4mA / cm 2 The test time is 300s after the flash voltage point A value appears. The test results are shown in Table 1.
[0065] Table 1 Test results of electrolyte conductivity and flash voltage
[0066]
[0067] As can be seen from Table 1, the electrolytes prepared in Examples 1-3 of the present invention have higher flash voltages than the comparative examples, and the conductivity of Example 3 and Comparative Example 1 with higher tannic acid content is significantly greater. This may be because the anode foil of the electrolytic capacitor has a pore structure of varying sizes on the surface, the main component is aluminum oxide, the surface is a transition layer between crystalline and amorphous, and the actual thickness of the anodized film is uneven. In the electrolyte formula of the present invention, the solvent is ethylene glycol, and the solutes ammonium dodecanedioate and ammonium sebacic acid can be well dissolved in ethylene glycol. After preparation and dissolution, they will not precipitate even at a lower temperature (5°C). Tannic acid has good solubility and migration properties in this system, so the increase in the proportion of tannic acid improves the conductivity of the electrolyte. The flash voltage enhancer in Examples 1-3 is a compound of tannic acid and plasma-treated silicon carbide, because tannic acid can form a stable barrier with the oxide film under the action of electric field force, and plasma-treated silicon carbide can be adsorbed in the pores of the oxide film, which effectively enhances the flash voltage of the electrolyte. The compound of tannic acid and plasma-treated silicon carbide produces a good synergistic effect, making the fire-resistant voltage of Examples 1-3 significantly better than that of Comparative Examples 1-4. The mass ratios of tannic acid to plasma-treated silicon carbide in Examples 1-3 are 1:1, 3:1, and 4:1, respectively, among which the flash voltage of Example 2 is the highest, which shows that the appropriate ratio can further enhance the flash voltage. This is because the particle size of silicon carbide is small, and a large amount of it is easy to cause local agglomeration, and an appropriate amount of tannic acid can inhibit this phenomenon. Compared with Example 2, in Comparative Example 3, the silicon carbide is not treated, and its conductivity and flash voltage are reduced. This may be because during the plasma strengthening process, high-energy plasma can interact with the surface of silicon carbide to form a special structure and chemical state on the surface of silicon carbide, thereby improving the surface properties of silicon carbide and enhancing the migration ability of silicon nitride and the performance of filling the holes of the anodized film.
[0068] A hollow structure shell, anode foil, cathode foil, electrolytic paper and lead wire were selected, the anode foil and cathode foil were curled and connected to the electrolytic paper to obtain a core bag, the core bag was dried and dehydrated, and poured into the electrolyte prepared in the embodiment and the comparative example respectively, and soaked at 60°C until the inside of the core bag was completely soaked with the electrolyte, and then loaded into the shell, packaged, and led out with a lead wire to prepare an electrolytic capacitor with a diameter of 35mm, a height of 50mm, a specification of 400V, and 470μF. The prepared electrolytic capacitor was loaded with a ripple current of 1.8A, and a service life test was carried out at 105°C. The results are shown in Table 2.
[0069] Table 2 Lifespan of electrolytic capacitors
[0070]
[0071] It can be seen from the test results in Table 2 that the capacitor constructed with the electrolyte of the embodiment of the present invention has a longer service life under the same test conditions. This is because the electrolyte containing tannic acid and plasma-treated silicon carbide has stronger thermal stability and chemical stability.
[0072] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte for an electrolytic capacitor, characterized in that: In parts by mass, it includes: 60-80 parts of solvent, 15-25 parts of solute, 0.1-0.5 parts of waterproof mixture, 0.1-0.5 parts of hydrogen remover, 0.5-2 parts of flash voltage enhancer; Wherein, the flash voltage enhancer comprises polyhydroxy polycarboxyl organic acid and plasma treated silicon carbide; The method for preparing plasma treated silicon carbide comprises: After washing the silicon carbide for 1 to 10 minutes in a mixed gas of oxygen and / or argon at a gas flow rate of 100 to 200 mL / min, a dielectric barrier discharge is used to treat the silicon carbide at a voltage peak of 1 to 10 kV for 1 to 10 minutes to obtain plasma-treated silicon carbide; The particle size of the silicon carbide is 0.02-5 μm; The mass ratio of the polyhydroxy-polycarboxyl organic acid to the plasma-treated silicon carbide is 1 to 5:1; The polyhydroxy-polycarboxyl organic acid is tannic acid.
2. The electrolyte for electrolytic capacitor according to claim 1, characterized in that: The solvent includes at least one of ethylene glycol, propylene glycol, glycerol, diethylene glycol, and n-butanol.
3. The electrolyte for electrolytic capacitor according to claim 1, characterized in that: The solute includes at least one of ammonium adipate, ammonium hydrogen azelate, ammonium dodecanedioate, and ammonium sebacate.
4. The electrolyte for electrolytic capacitor according to claim 1, characterized in that: The waterproofing mixture includes at least one of polymethacrylic acid, phosphoric acid, ammonium phosphate, hypophosphorous acid, ammonium hypophosphite, phosphorous acid, and ammonium phosphite.
5. The electrolyte for electrolytic capacitor according to claim 1, characterized in that: The hydrogen remover comprises at least one of nitrobenzyl alcohol, p-nitrobenzoic acid, resorcinol, o-nitroanisole and m-nitroacetophenone.
6. An aluminum electrolytic capacitor, comprising a hollow structure shell, an anode foil, a cathode foil and a lead wire, wherein the anode foil and the cathode foil are parallel to each other and penetrate the shell, and the anode foil and the cathode foil are led out by the lead wire, characterized in that: The shell stores the electrolyte for the electrolytic capacitor according to any one of claims 1 to 5.
Citation Information
Patent Citations
Anti-corrosion electrolyte for electrolytic capacitor
CN112908703A
High-voltage aluminum electrolytic capacitor and electrolyte
CN114783777A
Plasma surface treatment using dielectric barrier discharges
CN101573467A
Temperature-resistant electrolyte for aluminum electrolysis and application thereof
CN101866751A
Chip electrolytic capacitor and preparation method thereof
CN116564712A